Electricity consumption: a management proposal developed in R based on smart meters for power plants - Barquero-Álvarez, David Eladio (2021)
Costa Rican electricity matrix is already considered renewable due to the high running on clean sources and the near-zero use of fossil-fuels; however, it is possible to complement this sustainability by improving the management of electricity consumption in power plants. On the other hand, the change to smart meters recording data every 15 minutes is a fact in the country and it implies an opportunity to propose new ways of managing the energy consumption information to take advantage of its complete potential. In this paper an interactive digital dashboard developed in R is proposed, from where it is possible to manage the electricity consumption for both a hydroelectric and a thermal power plant, according to the previously identified requirements from the users and the existing data architecture, including smart meters. The dashboard is located at a web address, from where users access and navigate to visualize the defined analyses easily and friendly-user. The proposed solution becomes an aid to the management of electricity consumption by increasing the awareness of electricity usage. Since it is working for two different power plants technologies, it could be considered useful for other facilities.